Assessment of knowledge of pharmacotherapeutics amongst medical undergraduates of a tertiary care teaching hospital of Chhattisgarh, India: a questionnaire based study - Tabish, Ahmed; Swapnil, Kaikade; A., Khan Tanveer; B., Chandel N.; Anand, Rao; Chandresh, Mishra (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Knowledge of pharmacology forms the basis of rational pharmacotherapy practice. Teaching the medical students about systematic application of pharmacology in patients’ care forms an essential component. It facilitates the medical students to develop a methodical approach in solving patients’ clinical problems. Methods: A questionnaire-based study was conducted, at Government Medical College Rajnandgaon involving second year MBBS students. Total 100 students participated in the study. Results: Hundred percent of the students responded that pharmacology was presently taught to them, seventy nine percent of them agreed with the fact that pharmacology was preferred to pass the MBBS, eighty eight percent of them responded that in pharmacokinetics was the least preferred topic, ninety seven of them were not aware of the essential drug list. Their suggestions regarding the change in teaching methodology was recorded. Conclusions: This study concludes that efforts are needed to develop a curriculum that encompasses important aspects of clinical pharmacology and therapeutics along with incorporation of the useful suggestions by the undergraduate students.